Alkaline Earth Metal Complexes: Mixed Ligand Complexes of Alkaline-Earth Metal Salts of Some Organic Acids with 5,7-Dichloro Oxine - Prakash, Dahram; Kumar Yadav, Ashok (Asian Journal of Chemistry, 2010)
A number of mixed ligand complexes of alkaline-earth metal salts of some organic acids like 1-nitroso-2-naphthol (IN2N). o-nitrophenol (ONP), 2,4-dinitrophenol (DNP), salicylaldehyde (Sal. H) and salicylic acid (Sal. A) with 5,7-dichloro-oxine have been synthesized and characterized by elemental analysis, conductivity measurement and IR-spectral studies.